Water supplies of the South Platte River Basin - Gerlek, Stephen, author; Hendricks, David W., advisor; Radosevich, George E., committee member (Colorado State University. Libraries, 1977)
It has been told that early plains travelers declared the great arid region west of the Missouri River a desert which could never become the home of civilized man. While this may have been the prevailing sentiment of many, there were those who possessed the necessary insight to realize the vast potential of this land. John Wesly Powell, the great explorer, is credited with the observation that “all the great value of this territory has ultimately to be measured in acre-feet.” And so it was that water would become the life blood of the west, its availability determining and allowing for the very existence and prosperity of man in this region. Today, one out of every five persons in the western states receives water imported from a source one hundred or more miles away. The water supply system developed by the city of Denver, for example, is a complex physical and institutional infrastructure; the cash value of all its trans basin tunnels, dams, pipelines, etc. is the greatest of any in the world. The scarcity of water and its importance fostered a “get-your-gun” attitude concerning this resource which is manifested today by emotionally and politically controversial issues. This report examines the water supplies of the South Platte River Basin, within which is contained one of the more important agro metropolitan regions of the west and the center of Colorado's economy. The hydrologic and legal availability of water both within the basin and from sources without is addressed. The history of its water resources development is given to provide a context to view the present. Asserting that the basin is approaching apex development where substantial amounts of raw water are no longer available for development, the possible sources of supply for its future are discussed.
Keywords: Water-supply -- Nebraska -- Platte River Watershed